Thrombosis-on-a-chip: Prospective impact of microphysiological models of vascular thrombosis. (March 2018) - Pandian, Navaneeth K.R.; Mannino, Robert G.; Lam, Wilbur A.; Jain, Abhishek
Abstract: The most common pathology of the blood-vessel organ system is thrombosis or undesirable clotting of the blood. Thrombosis is life threatening as more than 25% of such cases lead to sudden death from stroke and myocardial infarction. Even though the process of thrombosis has been extensively investigated with animal models, its exact pathobiology in different blood vessels is not yet fully understood and drug assessment remains unpredictable. This is primarily because the cause for thrombus formation is multifactorial and depends on the interplay of flow patterns within the blood vessel, the vessel wall or endothelium, extracellular matrix, parenchymal tissue, and the cellular and plasma components of the blood. Current in vitro and animal models do not mimic or dissect this organ-level complexity faithfully. However, microfluidic technology has recently been deployed to effectively recapitulate blood-endothelial–epithelial interactions in the onset of thrombosis in blood vessels. This technology is promising because it permits inclusion of primary human cells and blood obtained from patients, which is currently lacking in other in vitro models of thrombosis. In this review, we summarize the current state-of-the-art and practices in microfluidics and expected improvements in this field that will impact basic understanding of thrombosis, drug discovery and personalized medicine. Highlights: Thrombus functions as a living organ that constantly interacts with its environment. Current models are inefficient in predicting thrombogenesis and for drug analysis. 3D co-culture microfluidic assays can assess organ-level thrombus regulation. Study of patient-specific physiology possible with thrombosis-on-a-chip technology.